Effect of season of birth and sex of kid on the production of live weaned single born kids in smallholder East African goat flocks in North East Zimbabwe - Ndlovu, L.R.; Simela, L. (Elsevier, 1996)
An amalgamated flock of traditionally managed Mashona Small East African goats was monitored over a 6 year period. Kids born in the hot dry season were heavier (p < 0.05) at 60, 90 and 180 d (6.4, 8.0 and 10.9 vs 5.7, 6.7 and 9.2 kg, respectively) than kids born in the hot wet season. Sex had no significant effect (p > 0.05) on weight increase. There was a steady decline in growth rates from age 15 d (60.2 g/ d) to weaning age of 180 d (41.7 g/d). Overall, 19.4% of the 294 kids born during the study period exited the flocks before age 180 d. Major causes of exits were lost kids and predation, which together accounted for 61% of exits by kids. Seasonal effects on exits were mainly at ages below 30 d where 10.3% of kids born in the hot dry season exited compared to 4.3% and 4.6% for the hot wet and cool dry seasons. Kidding intervals were 321 (s.e. 23.6), 325 (s.e. 30.9) and 259 (s.e. 50.1)d for does kidding in the hot dry, hot wet and cool dry seasons, respectively. Due to the slow growth rates and long kidding intervals the flock productivity in terms of weaned live kid weight (kg) per doe per year was low.